Capsicum carassense (Solanaceae), a new species from the Brazilian Atlantic Forest - Barboza, Gloria Estela (2020)
Capsicum carassense Barboza & Bianchetti sp. nov., a species from mid-elevation of the Atlantic Forest (Minas Gerais, Brazil) is described and illustrated. This endemic new species is distinguished from the most similar C. mirabile Mart. by its moderate to dense general pubescence, narrowly elliptic leaves andlarger calyx appendages and corollas. A key for the native Brazilian species of Capsicum growing in the state of Minas Gerais is also provided.